Breaking Intangible Barriers in English-as-an-Additional-Language Job Interviews: Evidence from Interview Training and Ratings. (28th November 2020) - Travers, Nick; Huang, Li-Shih
Abstract: This article reports a study that involved simulated job interviews with 27 high-proficiency English-as-an-additional-language (EAL) candidates and nine professional interviewers and that evaluated three conditions: a control group and two experimental groups (one receiving only personalized, training-focused feedback on interview skills immediately after the first interview, the other receiving both the same personalized feedback and a pragmatics-focused training session, also immediately after the first interview). As derived from the 2, 106 scores generated, the quantitative results showed that both experimental groups significantly outperformed the control group. The qualitative results from content analysis of the interviewers' 341 comments captured in video-stimulated recalls showed that various themes related to language ability featured most prominently in interviewer evaluations; the themes also differentiated above-average and below-average-rated candidates. The study underscores the extent to which communicative performance swayed interviewers' judgements above other variables; these judgements in turn may prove a disadvantage for EAL candidates in their job interviews and thus merit the critical awareness and reflection of EAL candidates, interviewers, and trainers alike.